The Promotion of Access to Employment for Persons with Disabilities - Cortez Segura, José Eduardo (2016)
The present article analyses the problems that occur in the contemporary world about the access to employment for persons with disabilities. Thus, beginning with the definition of disability and describing the support that has the Peruvian State to assume a social role, the article advances to describe the main ways of promotion of this kind of employment and the measures implemented in this matter.